2011
DOI: 10.1038/msb.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of proteome changes reveals new roles for transcript alteration in yeast

Abstract: By characterizing dynamic changes in yeast protein abundance following osmotic shock, this study shows that the correlation between protein and mRNA differs for transcripts that increase versus decrease in abundance, and reveals physiological reasons for these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
315
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(362 citation statements)
references
References 69 publications
(120 reference statements)
36
315
4
2
Order By: Relevance
“…2B, orange line). A similar result was recently observed for ∼2,500 proteins measured from bulk populations by mass spectrometry in response to osmotic shock (17). At steady state, protein abundance is determined by synthesis, degradation, and dilution rates.…”
Section: Significancesupporting
confidence: 58%
“…2B, orange line). A similar result was recently observed for ∼2,500 proteins measured from bulk populations by mass spectrometry in response to osmotic shock (17). At steady state, protein abundance is determined by synthesis, degradation, and dilution rates.…”
Section: Significancesupporting
confidence: 58%
“…Use of TMT proteomics to study microbial communities Prior proteomics studies using TMT-or isobaric tags for relative and absolute quantification-based isobaric chemical labeling have been applied exclusively to human tissues, plants and cultured isolates (for example, Dayon et al, 2010;Lee et al, 2011;Li et al, 2012;Westman et al, 2012;Chen et al, 2013;Paulo et al, 2013;Li et al, 2014). Here, we validate the TMT-based quantitative proteomics approach as applied to microbial communities, showing precise quantification of thousands of proteins across a large range of fold changes.…”
Section: Discussionmentioning
confidence: 84%
“…However, research in various organisms has also revealed that protein dynamics is often partly decoupled from RNA expression levels (e.g. recent data in (1)(2)(3)(4)(5)(6)). In Arabidopsis, especially diurnal transcript level fluctuations were not matched by corresponding changes in the detected proteome (7).…”
mentioning
confidence: 99%